Moisture sensitivity of crumb rubber modified modifier warm mix asphalt additive for two different compaction temperatures - Bilema, Munder A; Aman, Mohd. Yusri; Hassan, Norhidayah A; Ahmad, Kabiru A; Elghatas, Hamza M; Radwan, Ashraf A; Shyaa, Ahmed S (IOP Publishing, 2018)
Crumb rubber obtained from scrap tires has been incorporated with asphalt binder to improve the performance of asphalt mixtures in the past decades. Pavements containing crumbrubber modified (CRM) binders present one major drawback: larger amounts of greenhouse gas emissions are produced as there is rise in the energy consumption at the asphalt plant due to the higher viscosity of these type of binders compared with a conventional mixture. The objective of this paper is to calculate the optimum bitumen content for each percentage and evaluate the moisture sensitivity of crumb rubber modified asphalt at two different compacting temperatures. In this study, crumb rubber modified percentages was 0%, 5%, 10% and 15% from the binder weight, with adding 1.5% warm mix asphalt additive (Sasobit) and crush granite aggregate of 9.5mm Nominal maximum size was used after assessing its properties. Ordinary Portland Cement (OPC) used by 2% from fine aggregate. The wet method was using to mix the CRM with bitumen, the CRM conducted at 177°C for 30 min with 700rpm and Sasobit conducted at 120°C for 10 min with 1000rpm. As a result, from this study the optimum bitumen content (OBC) was increased with increased crumb rubber content. For performance test, it was conducted using the AASHTO T283 (2007): Resistance of Compacted Bituminous Mixture to Moisture-Induced Damage. The result was as expected and it was within the specification of the test, the result show that the moisture damage increased with increased the crumb rubber content but it is not exceeding the limit of specification 80% for indirect tension strength ratio (ITSR). For the temperature was with lowing the temperature the moisture damage increased.